Suggested Attitudes of Municipal Councilors in the Light of Empirical Research - Nogalski , Bogdan; Kozłowski , Andrzej J.; Czaplicka-Kozłowska, Iwona Z. (Studia Oeconomica Posnaniensia, 2016)
In Polish tradition, the commune council, due to the authority of a person's seat in it, was called the local parliament. In these bodies sat authoritative people, clever in the assessment of the people, and so made decisions accepted by everyone. It can be assumed that in the history of the local democracy in Poland of the 19th century, the persons managing the local dimension had the highest qualifications and incurred the greatest financial liabilities towards the commune. In the presented article, these issues were related to contemporary times, and therefore the problem of the evaluation of features was noted, which members of the general management of local authorities should have: the boards of the commune self-government. The problem discussed in the article is an identification of the features councillors of communes should have. The purpose for the examinations was to build the model/ standard of the councillor in the commune, based on the opinions of residents, clerks, and councillors. The article presented mainly the research results of the conducted examinations with respondents' techniques of Warmia and Mazury in the autumn of 2012.